Geometry Concept on the Motifs of Woven Fabric in Kefamenanu Community - Deda, Yohanis Ndapa; Amsikan, Stanislaus (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2019)
For the Kefamenanu community, the motif serves as the identity of the person who wears it. Nevertheless, the woven fabric must be present at cultural occasions, welcoming guests, and death ceremonies. The motifs of traditional woven fabric have not been developed by teachers to discuss the link between mathematics and local wisdom. The purpose of this research is to define and describe the mathematical concept of the motifs woven fabric to the students of primary and junior high schools. The present study uses a descriptive qualitative method to explain the geometry concept on the motifs of woven fabric. The ethnographic approach is also employed as an empirical and theoretical approach to provide description and analysis about a culture based on intensive field work. Collecting data were conducted using interviews and documentation. Interviews were conducted with several informants selected based on the consideration of researcher and suggestion by previous informant. Documentation was done using video recordings and photos. The results show the geometry concept of the motifs of woven fabric, such as reflection, rotation, translation, repetition, triangle and quadrilateral. The motifs of woven fabric owned by the Kefamenanu community contain particular local wisdom and are potentially used to convey the geometry concept in mathematics for primary and junior high schools.Â